Challenzyme Supplementation of High Expeller Copra Meal in Corn-animal Protein Diets for Broilers: Growth Performance, Nutrient Digestibility and Carcass Traits - Devi, Ashika; Diarra, Siaka Seriba; Mael, Sandy Hoffman (Indian Journal of Animal Nutrition, 2019)
A five-week experiment was conducted to investigate the effects of Challenzyme supplementation of expeller copra meal (ECM) fed in corn-animal protein-based diets on growth performance, nutrient digestibility, carcass and gut measurements of broilers. A total of 168, 9 days old Cobb 500 broilers were assigned to 8 diets consisting of 2 controls (with and without enzyme) and 6 other diets consisting 150, 300 and 450 g/kg ECM levels (with and without enzyme), were fed in three replicates of 6 birds each in a completely randomized design. Results showed significant interactions effects on growth parameters and fat digestibility. Feed intake and weight gain were reduced on 300 and 450 g/kg diets (P